The environmental dimension in the training of health professionals: conceptions held by professors in a public university - Arroyo, Ruth (2021)
Objective. Analyze the conceptions of teachers about the integration of the environmental dimension in the training of health professionals in a public university. Methods. Qualitative study, where 13 teachers selected by a socio-structural sampling participated. A semi-structured interview and the content analysis technique were applied using ATLAS.ti. Results. The teachers recognized limitations to incorporate the environmental dimension in health professionals, but they focus on the changes that would be needed for its integration at the macro and micro-curricular level. The analysis shows the link between the necessarychanges with awareness and socialization actions, political and administrative management, and proposals for infrastructure improvement. Conclusion. Teachers, despite the limitations, have proactive conceptions towards change, which would favor their participation in curricular reform processes towards training oriented towards sustainable development.